2016
DOI: 10.1007/s10596-016-9571-6
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale model reduction for shale gas transport in fractured media

Abstract: In this paper, we develop a multiscale model reduction technique that describes shale gas transport in fractured media. Due to the pore-scale heterogeneities and processes, we use upscaled models to describe the matrix. We follow our previous work [1], where we derived an upscaled model in the form of generalized nonlinear diffusion model to describe the effects of kerogen. To model the interaction between the matrix and the fractures, we use Generalized Multiscale Finite Element Method [13,17]. In this approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 46 publications
0
44
0
Order By: Relevance
“…In most of the previous studies, the gas diffusion in coal was viewed as a steady-state process, and the timeliness of this process was not considered, that is, the diffusion coefficient was treated as a constant Akkutlu et a., 2016;Yan et al, 2014). However, the aforementioned analysis indicates that the unipore diffusion model is not suitable for coal masses, so a multistage diffusion model should be used to characterize the dynamic diffusion process.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…In most of the previous studies, the gas diffusion in coal was viewed as a steady-state process, and the timeliness of this process was not considered, that is, the diffusion coefficient was treated as a constant Akkutlu et a., 2016;Yan et al, 2014). However, the aforementioned analysis indicates that the unipore diffusion model is not suitable for coal masses, so a multistage diffusion model should be used to characterize the dynamic diffusion process.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…where C M is molar mass of CH 4 , kg/mol;R is gas constant, J/(mol·K); 0 D is gas diffusion coefficient, m 2 /s, which in previous studies was generally viewed as a constant Akkutlu et al, 2016), but as discussed in section 1, it changes with the diffusion process. Based on related theoretical analyses and experimental investigations, put forward the dynamic diffusion coefficient model, which is given as follows:…”
Section: Gas Diffusion In Coal Seamsmentioning
confidence: 99%
“…Multiscale finite volume method for solution of the poroelasticity problem is presented in [29]. Generalized multiscale finite element (GMsFEM) for solution of the flow problems in fractured porous media is considered in [30,31]. In [32,33], we considered construction of the coarse grid problem for poroelasticity problem in heterogeneous media.…”
Section: Introductionmentioning
confidence: 99%
“…have noticed the big differences between kerogen and inorganic matrix in shale and treat them separately [10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, Akkutlu [12] adopted multiscale asymptotic analysis method to solve a one-dimensional dual-porosity continuum model and concluded that both the gas in-place and gas production rate depend on the content of kerogen in shale. Later, Akkutlu [13] employed the generalized multiscale finite element method (GMsFEM) to add the influence of fractures and extended the model to 2D. Based on Akkutlu's work, in 2016, Alexey [14] divided shale into kerogen and inorganic matrix and solved both the continuum subdomains by nonlinear parabolic equation, then utilized numerical homogenization technique through local problems to calculate macro parameters.…”
Section: Introductionmentioning
confidence: 99%